RIFFATERRE'S SEMIOTIC ANALYSIS OF THE SONG ATUNA TUFULI BY REMI BANDALI - Muhammad Nurfaizi Yuhmansyah; Sitti Wahidah Masnani; Haeruddin Haeruddin; Andi Agussalim; Mujadilah Nur (RADJA PUBLIKA, 2025)
Songs are one form of oral literature that has the power to convey messages through language and music. So the analysis of the meaning of the lyrics of the song Atuna Tufuli popularized by Shirine was carried out using Michael Riffaterre's semiotic analysis which focuses on the analysis of poetry (song lyrics). This study aims to find the meaning of the lyrics of the song Atuna Tufuli by describing namely (1) indirectness of expression, (2) heuristic and hermeneutic reading, (3) matrix, and (4) Model and hypogram (intertextual correlation). This study is a descriptive-qualitative type of research with a semiotic approach and the lyrics of the song Atuna Tufuli as its corpus. The design used in this study is a library study (Library Research). The results show that the lyrics of Atuna Tufuli by Remi Bandali utilize indirectness of expression to convey the complex meaning of love. (1) indirectness of expression includes: (a) Displacement of meaning. (b) distortion of meaning. (c) Creation of meaning. (2) Heuristic and Hermeneutic Readings describe the expression of suppressed feelings of love. (3) The matrix of these lyrics can be identified as